Secreted Bacterial Adenosine Deaminase Is an Evolutionary Precursor of Adenosine Deaminase Growth Factor. (16th October 2018) - Skaldin, Maksym; Tuittila, Minna; Zavialov, Andrey V; Zavialov, Anton V
Abstract: Adenosine deaminases (ADAs) play a pivotal role in regulating the level of adenosine, an important signaling molecule that controls a variety of cellular responses. Two distinct ADAs, ADA1 and adenosine deaminase growth factor (ADGF aka ADA2), are known. Cytoplasmic ADA1 plays a key role in purine metabolism and is widely distributed from prokaryotes to mammals. On the other hand, secreted ADGF/ADA2 is a cell-signaling protein that was thought to be present only in multicellular organisms. Here, we discovered a bacterial homologue of ADGF/ADA2. Bacterial and eukaryotic ADGF/ADA2 possess the dimerization and PRB domains characteristic for the family, have nearly identical catalytic sites, and show similar catalytic characteristics. Most surprisingly, the bacterial enzyme has a signal sequence similar to that of eukaryotic ADGF/ADA2 and is specifically secreted into the extracellular space, where it may potentially control the level of extracellular adenosine. This finding provides the first example of evolution of an extracellular eukaryotic signaling protein from a secreted bacterial analogue with identical activity and suggests a potential role of ADGF/ADA2 in bacterial communication.